PEMBUATAN WASIAT WAJIBAH BAGI ANAK ANGKAT YANG BERAGAMA ISLAM DIHADAPAN NOTARIS MENURUT KETENTUAN HUKUM ISLAM - RABITHAH KHAIRUL (PREMISE LAW JURNAL, 2016)
Its development adoption at this juncture not just separation of the juridical relationship with her biological parents, but by this time the problems of adopted children already developed to the problem of the Division of the inheritance. The existence of adopted children in succession at this point still being debated are always discussed, both in the circle of politicians, academics, and law enforcers. A will is a thing that can not be separated from the law. A will relating to the rights of power or responsibility that will run after someone dies, for example, a person she talked to other people in order to help educate his son later, paying debts or return an item ever dipinjamnya, on the other hand is also an obligation for people who can afford against children who have no parents, as a humanitarian mission and practice the teachings of the religion. Keywords: Wills Wajibah, A Foster Child, Notary Public